(untitled) (Global Scientific Review, 2023)
The article examines the morphological structure of karakul fur depending on the type of tanning and pH of the environment. Micrographs of the cross-section, surface and hair layer of tanned karakul with glutaraldehyde in acidic, alkaline and neutral media were obtained. The process of sorption of water vapor at a temperature of 20 °C in karakul specimens, tanning with chromium salts and glutaraldehyde has been studied.